Penegakan Hukum Pidana Terhadap Tindakan Pengemis Dan Gelandangan Di Kota Padang Berdasarkan Peraturan Daerah No 11 Tahun 2005 Tentang Ketertiban Umum Dan Ketentraman Masyarakat - Jimmy Aji Santuni; Sri Wahyuni; Helfira Citra (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2023)
Homeless people and beggars are social problems which are social problems in urban areas, not only in big cities but also in small towns. The acts of beggars and vagrants cause problems in society as well as existing laws or norms, begging in public places and vegrants are considered a social disease so that they can be categorized as a form of crime. According to criminal law it is prohibited and is a criminal act that deserves punishment, general criminal sanctions for this activity are regulated in the criminal code, however the regional government through the perda the act of beggars and homeless people violates the padang city regional regulation number 11 of 2005 concerning public order and public peace in article 2 paragraph (4) and article 4 paragraph (7), formulation of the problem 1) how is law enforcement carried out by the satpol pp against the crime of homeless people and beggars in padang city based on padang padang city regional regulation  number 11 of  2025 concerning public order and public peace? 2) what are the obstacles and efforts made by satpol pp in enforcing the law against beggars and homeless people in padang city based on padang city regional regulation number 11 of  2005? The research method is empirical, namely a legal research method that functions to see the law in a real sense and research how the law works in society. So far, beggars and homeless people in the city of Padang will only be given rehabilitation and some will be sent home after being in temporary shelter for selection. This selection process refers to Article 12 in the government Regulation of the Republic of Indonesia Number 31 of 1980 concerning beggars and Homeless. The obstacles faced by the Padang City Satpol PP in taking action against beggars and homeless people in public are: 1) internal factors, facilities and inferastrukture. 2) External factor, community legal awareness. Conclusion: 1) forms of law enforcement against acts of vagrancy and begging commited in public places so far rarely use criminal provision in dealing with thes action. In fact, the criminal provision against sprawl were previously regulated in the Padang City Regional Regulation 2)There are 2 obtacles that become obstacles for the Satpol PP, namely internal (lack of facilities and infrastructure) and external (lack of public awareness).